2015
DOI: 10.1517/14656566.2016.1118055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the IMPROVE-IT trial in the light of current and future lipid-lowering treatment options

Abstract: The results from IMPROVE-IT revalidated the concept that low-density lipoprotein cholesterol (LDL-C) levels are a clinically relevant treatment goal. This trial also suggested that further decrease of LDL-C levels (53 vs. 70 mg/dl; 1.4 vs. 1.8 mmol/l) was more beneficial in lowering CV events. This "even lower is even better" evidence for LDL-C levels may influence future guidelines and the use of new drugs. Furthermore, these findings make ezetimibe a more realistic option to treat patients with statin intole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 100 publications
2
29
0
1
Order By: Relevance
“…Similar results were obtained in the Open-Label Study of Long-Term Evaluation Against LDL-C (OSLER) trial with evolocumab [7]. However, the data concerning the safety of preserving very low LDL-C levels on long term are still limited [6].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were obtained in the Open-Label Study of Long-Term Evaluation Against LDL-C (OSLER) trial with evolocumab [7]. However, the data concerning the safety of preserving very low LDL-C levels on long term are still limited [6].…”
supporting
confidence: 71%
“…Beside IMPROVE-IT trial, another important trial ODYSSEY LONG-TERM (NCT01507831) with proprotein convertase subtilisin/ kexin type 9 (PCSK9) inhibitor -alirocumab, supported the hypothesis 'even lower is even better' for LDL-C levels [4], generating more arguments for lower LDL-C targets <50 mg/dl (1.3 mmol/l), in contrast with the current targets <70 mg/dl (1.8 mmol/l) for patients at the highest risk [5]. The same trial also confirmed that LDL-C goals below <25 mg/dl and even <15 mg/dl were not connected with the increase of any adverse events [5,6]. Similar results were obtained in the Open-Label Study of Long-Term Evaluation Against LDL-C (OSLER) trial with evolocumab [7].…”
mentioning
confidence: 99%
“…inhibitors (however it is worth mentioning that these studies were neither designed nor powered to investigate CV outcomes) and confirmed the safety of LDL-C reduction, to levels even below 25 mg/dL [6,7]. The results of the cardiovascular outcomes trials (CVOT) with these agents (FOURIER, ODYSSEY OUTCOMES) are expected in 2017 and 2018 [11,12].…”
Section: Overview Of the Marketmentioning
confidence: 98%
“…The combination led to lower LDL-C levels (53.7 vs 69.5 mg/dL) than simvastatin monotherapy, and importantly this translated to reduced risk of the primary endpoint, which was a composite of cardiac events (hazard ratio [HR] 0.936 [0.89 to 0.99]) [5]. However, surprisingly, despite these positive and significant results the US Food and Drug Administration (FDA) did not approve ezetimibe for use as an addition to statin therapy for reduction of CV events in patients with coronary heart disease (CHD) [6,7].…”
Section: Overview Of the Marketmentioning
confidence: 99%
See 1 more Smart Citation